UNLAWFUL DETENTION: A DISAPPOINTING JUDGMENT Alves v LOM Business Solutions (Pty) Ltd 2012 (1) SA 399 (GSJ) - J Neethling; JM Potgieter (Obiter, 2021)
In Alves v LOM Business Solutions (Pty) Ltd (2012 (1) SA 399 (GSJ); [2011] 4 All SA 490 (GSJ)) the plaintiff, who had been indicted for murder, was convicted in the High Court of attempted murder on 13 December 2005. Leave to appeal was granted immediately. The appeal was directed to the full bench of the division and was heard on 29 February 2008, more than two years later. The appeal was successful and the plaintiff’s conviction and sentence were set aside on 5 March 2008. The plaintiff claimed that the long interval of time between the granting of the leave to appeal and the hearing thereof should be attributed to the negligence of the defendants in that they failed to ensure that an appeal record was prepared within a reasonable time. He alleged that, as a result of the defendants’ breach of their duty, he was incarcerated for about 15 months longer than was reasonably necessary in the circumstances. (The first defendant was a firm responsible for preparing the transcript for his appeal hearing; the second defendant was the Minister of Justice and Constitutional Development, responsible for the overall administration of justice in the country.) The plaintiff claimed generaldamages for psychological pain and suffering and special damages for loss of earnings.